Volcanoes of the Azores Revealing the Geological Secrets of the Central Northern Atlantic Islands (Active Volcanoes of the World,, 2018)
The Azores archipelago consists of nine islands that emerge from the Azores Plateau in the Central Northern Atlantic, situated within the triple junction of the American, Eurasian and African lithosphere plates. Subaerial volcanic activity has been well known since the Pliocene and continues today, with several well-documented eruptions since the settlement of the islands in the fifteenth century. The origin of the Azores Plateau has been a matter of scientific debate and thus this book provides the first comprehensive overview of geological features in the Azores from volcanological, geochemical, petrological, paleontological, structural and hydrological perspectives.